Managing multiple and extensively drug-resistant tuberculosis and HIV. - Padayatchi, Nesri; Friedland, Gerald (Expert opinion on pharmacotherapy, 2007)
Global increases in multi-drug-resistant and extensively drug-resistant tuberculosis (TB), are threatening both TB and HIV treatment programs worldwide. Together, they raise concerns of a global epidemic of untreatable TB. In the developing world, the directly observed treatment, short course (DOTS) strategy is proving ineffective as available resources are being outstripped by the large number of patients needing treatment. Thus, TB treatment and outcomes are sub-optimal, and multi-drug resistant and extensively drug-resistant TB are on the rise.
Keywords: Anti-HIV Agents; Antitubercular Agents; Developing Countries; Directly Observed Therapy; Disease Outbreaks; Drug Resistance, Bacterial; Drug Resistance, Multiple; Health Personnel; HIV Infections; Humans; Prevalence; Treatment Outcome; Tuberculosis, Multidrug-Resistant; World Health